2010
DOI: 10.2174/138161210790232149
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and Cancer Therapy: The Emperor has NO Clothes

Abstract: The role of nitric oxide (NO·) as a mediator of cancer phenotype has led researchers to investigate strategies for manipulating in vivo production and exogenous delivery of this molecule for therapeutic gain. Unfortunately, NO· serves multiple functions in cancer physiology. In some instances, NO· or nitric oxide synthase (NOS) levels correlate with tumor suppression and in other cases they are related to tumor progression and metastasis. Understanding this dichotomy has been a great challenge for researchers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 90 publications
2
98
0
Order By: Relevance
“…Likewise, × NO and its nitrogen oxide products can affect cancer therapy either positively or negatively (Hickok and Thomas, 2010). The present study extends our work in vitro to tumor cells and shows significant oxidative chemistry of × NO with VP-16.…”
Section: Discussionsupporting
confidence: 77%
“…Likewise, × NO and its nitrogen oxide products can affect cancer therapy either positively or negatively (Hickok and Thomas, 2010). The present study extends our work in vitro to tumor cells and shows significant oxidative chemistry of × NO with VP-16.…”
Section: Discussionsupporting
confidence: 77%
“…This latter observation may mirror the known dichotomic role of NO in the regulation of oncogenesis that may result in pro-or anti-tumor effects depending on concentration, the microenvironment and local or peripheral localization within the tumor. This bimodal action of NO has led this molecule to be considered both as a target for cancer therapy and an anti-cancer agent (19)(20)(21). The different contribution of endogenously produced and exogenously-administered NO on the dysregulated growth of A375 cells, and possibly other cancer cells, should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in inducible nitric oxide synthase (iNOS) expression is associated with early recurrence [114] and metastatic processes [115,116]. Belgorosky et al [117] showed that human colorectal adenocarcinoma cells that express iNOS are more invasive than the non-iNOS-expressing cells.…”
Section: Antimetastatic Effectsmentioning
confidence: 99%